2021
DOI: 10.1038/s41467-021-24737-x
|View full text |Cite
|
Sign up to set email alerts
|

Harmful R-loops are prevented via different cell cycle-specific mechanisms

Abstract: Identifying how R-loops are generated is crucial to know how transcription compromises genome integrity. We show by genome-wide analysis of conditional yeast mutants that the THO transcription complex, prevents R-loop formation in G1 and S-phase, whereas the Sen1 DNA-RNA helicase prevents them only in S-phase. Interestingly, damage accumulates asymmetrically downstream of the replication fork in sen1 cells but symmetrically in the hpr1 THO mutant. Our results indicate that: R-loops form co-transcriptionally in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 82 publications
6
62
0
Order By: Relevance
“…We observed RNA:DNA hybrid hyper-accumulation during this type of collisions in sen1 mutants and a minor increase of these structures in co-directional clashes. These results are consistent with the previously described dynamic of hybrid accumulation in sen1 mutants at some highly-expressed genes ( 24 ) and genome-wide ( 33 ). While our findings are not in contrast with the notion that R-loops tend to accumulate in both types of collisions ( 6 , 31 ), they do suggest that R-loops contribute to fork arrest only in head-on clashes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed RNA:DNA hybrid hyper-accumulation during this type of collisions in sen1 mutants and a minor increase of these structures in co-directional clashes. These results are consistent with the previously described dynamic of hybrid accumulation in sen1 mutants at some highly-expressed genes ( 24 ) and genome-wide ( 33 ). While our findings are not in contrast with the notion that R-loops tend to accumulate in both types of collisions ( 6 , 31 ), they do suggest that R-loops contribute to fork arrest only in head-on clashes.…”
Section: Discussionsupporting
confidence: 93%
“…In Sen1-depleted cells, head-on highly transcribed RNAPII genes accumulate R-loops ( 24 , 33 ) and form an impenetrable barrier to replication fork ( 34 ). The activation of dormant origins near the collision sites is a mechanism to rescue stalled replication forks, while the protection of replisome prevents the nuclease-mediated processing of R-loops at the fork ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…RNAPII accumulation was also observed in rnh1𝚫 rnh201𝚫 cells suggesting that RNase H is required at this locus for efficient RNAPII release. Consistently, R-loops were detected, both by H-CRAC and DRIP (San Martin-Alonso et al, 2021;Wahba et al, 2016) immediately upstream of the paused polymerase (Figure S5B). Interestingly, we also noticed the occurrence of transcription upstream and antisense of RDN5 directed towards the close rARS (ARS1200) replication origin (Figure 5C), which was only observed in replicating cells and was also RNases H dependent.…”
Section: Roles Of Sen1 and Rnases H In Limiting Rnapii Transcription ...supporting
confidence: 62%
“…RNAPII CRAC is also shown for evaluating the R-loop signals relative to transcription. For the directional DRIP-seq (San Martin-Alonso et al, 2021), the H-CRAC and the RNAPII CRAC only the strand of the target gene is shown. B) Overlap of the genes containing the highest signals (levels higher than the mean plus one standard deviation) defined by the directional DRIP-seq (San Martin-Alonso et al, 2021) and by H-CRAC (Rnh1 or Rnh201).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, abolishment of either the THO or TRAMP complex has been shown to increase R-loop-associated genome instability [22, 36, 37, 51]. Recently, the THO complex was shown to prevent R-loop formation throughout the cell cycle whereas other factors such as Senataxin only resolve R-loops during S-phase [52]. We previously showed that R-loops form preferentially at expanded CAG tracts in vivo and that increasing R-loop stability by removing both RNase H1 and RNase H2 proteins using a rnh1Δrnh201Δ double mutant further increased CAG repeat fragility [7].…”
Section: Resultsmentioning
confidence: 99%